Селекція яблуні на поліплоїдному рівні - Захарова, В.А.; Захаров, М.В.; Хилько, В.Т. (Фактори експериментальної еволюції організмів, 2013)
Aims. To work out new methods changes of heredity, that would give an opportunity in a greater scale to induce mutational and recombination changeability. Methods. Cytologic research on the generally accepted methodology. Results. Through the study of diploid – tetraploid chimeras derived from experimental mutagenesis, the number of violations found in the different phases of meiosis. Characterized some diploid – tetraploid chimeras with valuable economic and biological traits.